(untitled) (Journal of Student Affairs in Africa, 2026)
The transition from high school to university presents significant challenges, particularly for students from historically marginalised communities and under-resourced schools, heightening risks of attrition and delayed progression. This affirms the value of integrated, intentional, equity-focused proactive early support, which the University of KwaZulu- Natal’s (UKZN) Academic Monitoring and Support (AMS) Policy promotes. This study examines first-year students’ experiences of equity-focused academic advising within orientation at the College of Humanities (CHUM), which enrols up to 60% of first-year students from quintile one to three schools. The article contributes to scholarship in two ways. First, through a case-study approach, it demonstrates how proactive academic advising promotes social justice. Second, it draws on two complementary frameworks – Nancy Fraser’s social justice framework assesses whether interventions address recognition, representation, and redistribution. Alf Lizzio’s Five Senses of Student Success frames students’ experiences across the domains of successful transition (capability, connectedness, purpose, resourcefulness, and academic culture). Data were collected from the student feedback survey, with 531 of the approximately 1,000 first-year students who participated in the intervention in 2025 responding. Findings indicate students’ enhanced sense of capability, resourcefulness, connectedness, purpose, and engagement with academic culture. Challenges with digital literacy, connectivity, and timing of data rollout contributed to low participation, highlighting barriers to achieving participatory parity. Implications for academic advising practice and approaches are discussed, and areas for further research are proposed.